Pneumomediastinum, pneumothorax and subcutaneous emphysema after tracheostomy closure. When less is more - Lazzarotto, Andrea; Tel, Alessandro; Vetrugno, Luigi; Cereser, Lorenzo; Sembronio, Salvatore; Di Cosola, Michele; Bove, Tiziana; Robiony, Massimo (Acta Biomedica Atenei Parmensis, 2022)
Pneumomediastinum is a threatening complication that might occur after tight surgical closure of tracheostomy is performed. Physiopathology of this condition is based on several factors, including direct trauma to the tracheal wall caused by surgical maneuvers or insufficient closure of soft tissue layers which do not seal air leakage. In this paper we explore this phenomenon by reporting the case of one patient undergoing surgical closure of tracheostomy after two weeks, who later developed subcutaneous emphysema followed by pneumomediastinum. Physiopatology is analyzed and management strategies for this condition are suggested based on our experience.